2022
DOI: 10.1145/3507901
|View full text |Cite
|
Sign up to set email alerts
|

Face Image Quality Assessment: A Literature Survey

Abstract: The performance of face analysis and recognition systems depends on the quality of the acquired face data, which is influenced by numerous factors. Automatically assessing the quality of face data in terms of biometric utility can thus be useful to detect low-quality data and make decisions accordingly. This survey provides an overview of the face image quality assessment literature, which predominantly focuses on visible wavelength face image input. A trend towards deep learning based methods is observed, inc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 169 publications
(309 reference statements)
0
47
0
Order By: Relevance
“…2. The used subset of the FRGCv2 dataset has good-quality face images which allows to analyse the sole impact of fun selfie filters on FR modules in the absence of quality-related factors [54], e.g., variations in pose or illumination.…”
Section: Fun Selfie Filter Databasementioning
confidence: 99%
“…2. The used subset of the FRGCv2 dataset has good-quality face images which allows to analyse the sole impact of fun selfie filters on FR modules in the absence of quality-related factors [54], e.g., variations in pose or illumination.…”
Section: Fun Selfie Filter Databasementioning
confidence: 99%
“…Face quality estimation From the results, it can be observed that the performance of FaceQnet and SER-FIQ decreases as the coverage of facial tattoos and paintings on a face become large. Since face quality estimation measures the utility of a facial image for face recognition [51], the observations are expected since for the comparison and features extraction module of both ArcFace and COTS a decrease in biometric performance was observed for facial tattoos and paintings compared to facial images without such manipulations. Feature extraction and comparison In the conducted experiments, we showed that facial tattoos and paintings significantly impact face recognition systems' ability to extract face features and recognise individuals.…”
Section: Feature Extraction and Comparisonmentioning
confidence: 99%
“…Beyond the vulnerability of face recognition due to facial masks, Fang et al [11] further analysed security critical issues in terms of face presentation attacks and the detectability of these attacks when wearing a mask or when a real mask is placed on the attack. Other works focus on relating the FIQ to morphing faces [14], face parts [13], image quality [12] or in a review [30].…”
Section: Related Workmentioning
confidence: 99%